Benefits that attract industry to implement ISO 28000 to secure supply chain - Wong, Huei Ing; Sorooshian, Shahryar; Muzamir, Hasan (UIKTEN - Association for Information Communication Technology Education and Science, 2019)
ISO 28000 is an international standard that requires specific qualifications in the security management system and it includes critical aspects that are related to security pledge in the supply chain. Supply chain security is one of the components of an organization’s strategy to secure their supply chain from the threat. Supply chain and organization that implement supply chain security mainly protect their chain from any risk that can damage their supply chain. ISO 28000 has the reason to affect industry to use it in order to protect supply chain process. Based on a literature review, this study is adding a list of benefits to the basic supply chain security that attracts industry to implement ISO 28000. Researchers believe that this study helps the industry in supply chain performance with the related information and reference about ISO 28000.